School Evaluation for Quality Improvement as The Gaze - Tumlovskaja, Jelizaveta; Ruškus, Jonas (Acta Paedagogica Vilnensia, 2022)
Within this paper, the authors examine the school performance quality assessment system in Lithuania from the standpoint of pedagogical staff who find themselves in the status of the assessed. The philosophical concept of The Gaze is used for the interpretation of the results of a quantitative and qualitative survey. The concept of the Gaze, as conceptualized by Sartre and Foucault, helps to understand the sense of tension between freedom and control as experienced by pedagogical staff who find themselves in the status of the assessed. The authors, by applying principles of phenomenological interpretative analysis and descriptive statistics, examine the process of school performance quality assessment as experienced by teachers. The informants identify themes such as stress, distress, work simulation, and creativity restrictions. The authors conclude that school performance quality assessments do emerge as the Gaze, and furthermore as a dilemma of communication known as the Double Bind, when at the same time contradictory objectives are held, and a regressive state of stress and distress is generated as a result. On the bases of results of their research, the authors suggest that the actual school performance quality assessment system in Lithuania must be fundamentally improved by applying the empowering consultancy approach, while measures of quality assessment should be focused on objective indicators of school performance quality assessment.
Keywords: general education school; quality assessment of general education schools; philosophical concept of The Gaze; freedom; control